Green Infrastructure Development within Urban Environment provided by Privately Owned Public Spaces - Stokmane, Ilze; Dupate, Marta (Landscape Architecture and Art, 2023)
Since the industrialisation era, there has been a trend towards radial sprawl, rapid development and concentration of people in the largest cities. Historically, people needed space outside their homes to interact and communicate to each other. In the city it was provided by public open space, forming the centres of social life. The conditions and opportunities for people to use outdoor space have also changed with changing eras and political power settings, along with the scale of development, security concerns and ownership of space in the city. The aim of the study is to explore the nature of Privately Owned Publicly – Accessible Spaces (POPS) and their potential development contribution to urban green infrastructure, developing design and planning recommendations for the development of Privately Owned Publicly – Accessible Spaces in the urban environment. The research carried out during the literature review and analysis of city plans of the cities introduced POPS program shows the relevance of the topic of private ownership of public open space in the world’s major metropolises, but that it is conceptually possible to adapt it to smaller-scale urban planning, for example by applying it to private investors and developers in their requirements for new buildings and sites development.